Analisis Nilai Tambah Tempe Biji Trembesi Pada Home Industry di Desa Cadaskertaja Kabupaten Karawang - Nugraha, Krisna Fernanda Adji; Wulandari, Yeni Sari; Mahatmayana, I Ketut Manu (JURNAL AGROPLASMA, 2024)
Trembesi seeds can be used as an alternative raw material for making tempeh considering the erratic fluctuations in soybean prices. This research aims to analyze how much income there is from the business of processing tamarind seeds into tempeh and to analyze the added value of the business of processing tamarind seeds into tempeh in the home industry in Cadaskertajaya Village, Karawang Regency. The data collection technique used was purposive sampling. Researchers used one respondent, namely the owner of the tempe trembesi home industry. This research uses primary data and secondary data. The data analysis method used is a quantitative descriptive method. Quantitative descriptive analysis is used to analyze the business which includes analysis of costs,revenues, income, and added value (added value) for domestic tempe trembesi industry products. The results of the analysis show that the total costs used for processing trembesi bean tempeh are IDR 463,333.2 per month. The average revenue for tempe seeds from trembesi is IDR 720,000 per month. The income obtained by the home industry of tempe seeds from trembesi was IDR 256,666.8 and the profitobtained by the home industry by selling 1 kg was IDR 21,388.9 or a profit of IDR 356.5 / pack. The added value obtained in one month is IDR 51,648 per kg of raw material, which means that every processing of one kg of trembesi seeds into tempeh provides an added value of IDR 51,648 with a value-added ratio of around 86% per kg. Keywords: home industry, revenue, tempe trembesi, value added